2022
DOI: 10.1146/annurev-pharmtox-030121-122314
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of TRPC Channels and Its Potential in Cardiovascular and Metabolic Medicine

Abstract: Transient receptor potential canonical (TRPC) proteins assemble to form homo- or heterotetrameric, nonselective cation channels permeable to K+, Na+, and Ca2+. TRPC channels are thought to act as complex integrators of physical and chemical environmental stimuli. Although the understanding of essential physiological roles of TRPC channels is incomplete, their implication in various pathological mechanisms and conditions of the nervous system, kidneys, and cardiovascular system in combination with the lack of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 165 publications
0
16
0
Order By: Relevance
“…Transient receptor potential canonical (TRPC) proteins, regulating intracellular Ca 2+ , K + , and Na + , are involved in a variety of physiological and pathological processes in cardiovascular system (64). It has been reported that TRPC3 is a risk factor deteriorating the pathological cardiac remodeling (65,66).…”
Section: Transient Receptor Potential Canonical 3 (Trpc3)-nadph Oxida...mentioning
confidence: 99%
“…Transient receptor potential canonical (TRPC) proteins, regulating intracellular Ca 2+ , K + , and Na + , are involved in a variety of physiological and pathological processes in cardiovascular system (64). It has been reported that TRPC3 is a risk factor deteriorating the pathological cardiac remodeling (65,66).…”
Section: Transient Receptor Potential Canonical 3 (Trpc3)-nadph Oxida...mentioning
confidence: 99%
“…Following the proof-of-concept brain slice assay we have tested, we consider BTDAzo as a valuable tool to investigate the various roles of TRPC5 (and so distinguish them from the distinct roles of TRPC4) in brain function, including their potential in the study and treatment of metabolic disease. [12] We believe this is also the first report of azobenzothiadiazines as photoswitches for cell biology. It can give favourably complete bidirectional photoswitching with rapid response under biologically available wavelengths, and its easy synthesis and handling recommend it for use towards other photopharmaceuticals.…”
Section: Discussionmentioning
confidence: 67%
“…To find out the possible contribution of genetic variants to this variation, we searched exome sequencing data in COSMIC ( https://cancer.sanger.ac.uk/cosmic ) and identified a hemizygous p.R175H missense mutation in TRPC5 in the TC-71 cell line not present in the DMS-114 cell line. This gene encodes the protein TRPC5, which forms homo- and heterotetrameric, nonselective cation channels permeable by Ca 2+ and Na + ( 31 , 32 , 33 , 34 , 35 , 36 , 37 ). Based on several pathogenicity prediction algorithms including SIFT ( 38 ) and PolyPhen-2 ( 39 ), this mutation is considered tolerable and benign.…”
Section: Resultsmentioning
confidence: 99%
“…High-quality chemical probes are powerful tools in target validation studies and can serve as useful starting points for drug development, especially when combined with genetic approaches. In our recent reviews, we highlighted the use of small-molecule modulators of TRPC1/4/5 channels to complement genetic approaches in dissecting the different roles of specific TRPC1/4/5 channels across species, tissues, and pathologies ( 36 , 37 ). However, even high-quality chemical probes are likely to have off-targets, and potency and selectivity of a chemical probe may be dependent on factors such as cellular context, mode of application, and treatment time.…”
Section: Discussionmentioning
confidence: 99%